Game cultures as sub-creations: case studies on religion & digital play - Hemminger, Elke (Online - Heidelberg journal of religions on the internet, 2014)
As online and ofﬂine spaces, digital and analogue worlds merge into each other and saturate our everyday lives, concepts of reality and its social construction need re-thinking. Digital game cultures, formerly often regarded as not only separate from reality, but also secondary in their importance for ,real lifeʻ, can give us insight into processes of cultural construction und re-construction, relevant for our mediatised society in general.This paper analyzes digital game cultures as sub-creations (Tolkien 1947) that are consistent, signiﬁcant and serve as comments on and additions to society. Focusing on religious elements in digital games, the paper states that game cultures reﬂect cultural practice in general and therefore contribute to the social construction of reality in essential ways.The paper is based on the results of several case studies on digital games during which a system to categorize digital games concerning the way they use religious elements was developed, going beyond existing game categories.The paper will introduce these classiﬁcations in order to support the assumption that religion in games can be seen not only as a key element in game cultures, but also as a reﬂection of social attitude towards and social status of religion in a wider prospect. Following this assumption, the paper will show how the analysis of digital games and their religious contents can help us observe and understand processes of social reality construction that might not be accessible or visible in other social contexts.